Ask the River: A Public Art and Placemaking Project. (19th August 2021) - Billings, Elizabeth; Lovett, Evie; Wasserman, Andrea
Abstract: Intertwining people and place, Ask the River is a public art and placemaking project reconnecting the Brattleboro, Vermont community to the nearby Connecticut River. Ask the River is guided by the Abenaki understanding that people and place are one: we are the River, the River is us. Three artists and multiple community partners create public art for community–a riverscape of shimmering kinetic sculpture spanning the town's parking garage–and in community, in workshops using the hands‐on, accessible and engaging process of cyanotype. The River is inspiration and guide. The purpose of Ask the River is for the Brattleboro community to explore seeing ourselves as a part of, not separate from, the River: to create pathways of reconnection, to enable us to hear its voice.